A case of cytokine release syndrome accompanied with COVID‐19 infection during treatment with immune checkpoint inhibitors for non‐small cell lung cancer. Issue 20 (8th September 2022) - Murata, Daiki; Azuma, Koichi; Tokisawa, Saeko; Tokito, Takaaki; Hoshino, Tomoaki
Abstract: Cytokine release syndrome (CRS) is a systemic inflammatory disease caused by a variety of factors, including infections and certain drugs. A 70‐year‐old man who was diagnosed with a postoperative recurrence of lung adenocarcinoma received nivolumab, ipilimumab, pemetrexed and carboplatin every 3 weeks for two cycles followed by nivolumab and ipilimumab, which resulted in a partial response. Four days after the dose of nivolumab, the patient returned with diarrhea and fever. The patient was diagnosed with COVID‐19 infection accompanied by severe colitis. Although intensive care was performed, the patient suddenly went into cardiopulmonary arrest. Examination revealed an abnormally high interleukin‐6 level, suggesting CRS. This is the first report of a patient with CRS accompanied with COVID‐19 infection during treatment with ICIs. Cytokine release syndrome (CRS) is a systemic inflammatory disease caused by a variety of factors, including infections and certain drugs. Here, we report a case of non‐small cell lung cancer with CRS caused by COVID‐19 infection during treatment with nivolumab and ipilimumab. Fever is a common event in cancer patients, especially in COVID‐19‐infected patients, but when fever develops during cancer immunotherapy, CRS should always be kept in mind. Abstract : Cytokine release syndrome (CRS) is a systemic inflammatory disease caused by a variety of factors, including infections and certain drugs. Here, we report a case of non‐small cell lung cancer with CRS caused by COVID‐19 infection during treatment with nivolumab and ipilimumab. Fever is a common event in cancer patients, especially in COVID‐19‐infected patients, but when fever develops during cancer immunotherapy, CRS should always be kept in mind.